2018
DOI: 10.3390/ijerph15040686
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment and Influencing Factor Analysis of Residential Indoor PM2.5 in Beijing

Abstract: In order to identify the sources of indoor PM2.5 and to check which factors influence the concentration of indoor PM2.5 and chemical elements, indoor concentrations of PM2.5 and its related elements in residential houses in Beijing were explored. Indoor and outdoor PM2.5 samples that were monitored continuously for one week were collected. Indoor and outdoor concentrations of PM2.5 and 15 elements (Al, As, Ca, Cd, Cu, Fe, K, Mg, Mn, Na, Pb, Se, Tl, V, Zn) were calculated and compared. The median indoor concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 76 publications
(174 reference statements)
2
27
0
Order By: Relevance
“…These elements are presumed to be emitted from metals in the boiler and its associated ducting rather than from the fuel itself. Zn is also reported to be released during cooking with gas stoves [ 78 , 79 , 80 , 81 ]. However, in Table 3 , unlike factor 1, the I/O ratio for factor 3, which is slightly lower than 1, indicates that the effects of the outdoor sources are larger than those of the indoor sources.…”
Section: Resultsmentioning
confidence: 99%
“…These elements are presumed to be emitted from metals in the boiler and its associated ducting rather than from the fuel itself. Zn is also reported to be released during cooking with gas stoves [ 78 , 79 , 80 , 81 ]. However, in Table 3 , unlike factor 1, the I/O ratio for factor 3, which is slightly lower than 1, indicates that the effects of the outdoor sources are larger than those of the indoor sources.…”
Section: Resultsmentioning
confidence: 99%
“…The annual average concentrations of heavy metals in PM 2.5 in various areas of Nanjing are shown in Table 2 and Figure 5 and are compared with other domestic and international regions and international air quality guidelines [11,33,34]. The concentrations of atmospheric heavy metals in Nanjing were generally high, especially V and Ti.…”
Section: Seasonal Distribution Of Pm 25 -Bound Heavy Metal Concentramentioning
confidence: 99%
“…Numerous IoT-based air quality monitoring systems using micro-sensors for data collection have been proposed, including open source technologies for data processing and transmission [18]. According to an IAQ analysis [19], it has been reported that indoor PM 2.5 pollution mainly comes from outdoor sources. In another study, three typical activities such as a having fireplace in the house, cooking with kitchen appliances and toasting were investigated, and indoor pollutant levels such as PM 2.5 , PM 10 and VOC were found to be above the limit values [20].…”
Section: Introductionmentioning
confidence: 99%